Historical Influences on Contemporary Tobacco Use by Northern Plains and Southwestern American Indians - Kunitz, Stephen J. (Am J Public Health, 2016)
There are great differences in smoking- and tobacco-related mortality between American Indians on the Northern Plains and those in the Southwest that are best explained by (1) ecological differences between the two regions, including the relative inaccessibility and aridity of the Southwest and the lack of buffalo, and (2) differences between French and Spanish Indian relations policies. The consequence was the disruption of inter- and intratribal relations on the Northern Plains, where as a response to disruption the calumet (pipe) ceremony became widespread, whereas it did not in the Southwest. Tobacco was, thus, integrated into social relationships with religious sanctions on the Northern Plains, which increased the acceptability of commercial cigarettes in the 20th century. Smoking is, therefore, more deeply embedded in religious practices and social relationships on the Northern Plains than in the Southwest.